First report of two genera Angustibracon Quicke and Pseudospinaria Enderlein (Hymenoptera: Braconidae) from Vietnam, with redescriptions of species - Khuat, Dang Long; Nguyen , Van Dzuong; Nguyen, Duc Hiep (Academia Journal of Biology, 2023)
Two small genera of the subfamily Braconinae, Angustibracon Quicke, 1987 and Pseudospinaria Enderlein, 1905, are reported for the first time from Vietnam. Two Angustibracon species, Angustibracon leptogaster Cameron and Angustibracon maculiabdominis Zhou & You and one Pseudospinaria species, Pseudospinaria attenuata (Westwood) are newly recorded for Vietnam’s braconid fauna. Additionally, the species are redescribed and illustrated. An illustrated key to the two known Augustibracon species and a mapped distribution of species in Vietnam are also given.